On-Line Parity Control Enhances 1149.1 BST Reliability - José Miguel Vieira dos Santos (1999)
The 1149.1 BST std is nowadays being proposed in several applications for on-line operation, but it doesn't provide any facility to verify the integrity and correctness of scanned data, since it was not designed to do so off-line. However, when the scan data is used for immediate decisions, we need to have confidence in the string entering or leaving the target IC. In this paper we show how the BST controller may read the parity of this string immediately after the scan operation, with almost no changes to the TAP controller.